The nitric oxide formation in anode baking furnace through numerical modeling - Prajakta Nakate (Elsevier, 2021)
Thermal nitric-oxide (NOx) formation in industrial furnaces due to local overheating is a widely known problem. Various industries made significant investments to reduce thermal NOx by varying the operating conditions and designs of the furnace. It is difficult to find the optimal operating conditions that minimize NOx formation in the furnace by trial and error methods. The high temperature in the furnace complicates performing experiments in the furnace. Numerical modeling can provide significant information in such cases. Therefore, the objective of this paper is to obtain a numerical model of the furnace in such a way that the operating conditions can be varied and examined.In this paper, a three-dimensional steady-state finite element model for the anode baking industrial furnace is discussed. The COMSOL Multiphysics software is used for modeling the non-premixed turbulent combustion and the conjugate heat transfer to the insulation lining. The cfMesh software is used for obtaining the mesh. The results show that the simulated temperature agrees well with the measured data from our industrial partner in regions distant from the flames. The analysis shows that by decreasing the fuel mass flow rate and increasing the fuel pipe diameter by 45%, the peak in thermal NOx ppm generated in the furnace decreases by 42%. The model is limited by the use of a single-step chemistry mechanism with an eddy dissipation combustion model and a simplified approach for radiation, such as the P1 approximation model. The model can be further improved by considering a detailed chemistry mechanism model for combustion and a discrete ordinate model for radiation.